THE STUDY OF NARRATIVE SEMIOTICS IN THE STORY OF ISRA MI’RAJ - Iwan Marwan; Wildan Taufiq (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2019)
The book of Bainama: Qishshah al-Mi'rȃj (BQM) by Imam Sheikh Najmuddin Al-Ghoithy Al-Dardiri, is an old literary works in the form of narrative prose (natsr qashashy). Therefore this research use the paradigm of A. J. Greimas that focused on how to sequence, and narrative aspects isotopy on the story of isra ' Ascension in the book